Higher serum vitamin D levels are associated with decreased odds of obstructive lung disease in the general population: an NHANES analysis (2007–2008 to 2009–2010) - Mohamed Ismail Seedahmed; Aaron D Baugh; Jordan A Kempker (BMJ Open Respiratory Research)
Background Obstructive lung disease is a significant cause of morbidity and healthcare burden within the USA. A growing body of evidence has suggested that vitamin D levels can influence the course or incidence of obstructive lung disease. However, there is an insufficient previous investigation of this association.Study design and methods We used the National Health and Nutrition Examination Survey (NHANES) cycles 2007–2008 and 2009–2010 spirometry results of individuals aged 40 years and older to assess the association between serum 25-hydroxyvitamin D levels and obstructive lung disease, as defined by the American Thoracic Society using the lower limit of normal. We used stage multivariate survey-logistic regression.Results The final model included age, gender, body mass index, pack-years smoking history, season, income-to-poverty ratio and race/ethnicity. In the primary analysis using vitamin D as a continuous variable, there was no association between vitamin D levels and obstructive lung disease. We noted a trend between ‘other Hispanic’ self-identified race and serum vitamin D levels wherein higher levels were associated with higher odds of obstructive lung disease in this ethnicity, but not among other racial or ethnic groups (OR (95% CI)=1.40 (0.98 to 1.99), p=0.06). In a secondary analysis, when vitamin D was measured as a categorical variable, there was a significant association between the highest levels of serum vitamin D levels and lesser odds of obstructive lung disease (OR (95% CI)=0.77 [0.61 to 0.98], p=0.04).Conclusions Higher serum vitamin D levels among adults are associated with decreased odds of obstructive lung disease in the general population. Results among non-Mexican Hispanic participants highlight the need for further research in minority populations. More work is needed to address the course and incidence of lung disease in the USA.